2016
DOI: 10.18202/jam23026332.14.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompensasi dan Kepuasan Kerja terhadap Komitmen Organisasional Perawat dan Bidan Kontrak di RS Bhayangkara Hasta Brata Batu Malang

Abstract: This study aims to determine the effect of compensation and job satisfaction of nurses and midwives to organizational commitment in Hasta Brata Keywords: compesation, job satisfaction, and organisasional commitmentAbstrak: Penelitian ini bertujuan untuk mengetahui pengaruh kompensasi dan kepuasan kerja perawat dan bidan terhadap komitmen organisasional di RS Bhayangkara Hasta Brata Batu Malang. Desain penelitian ini menggunakan pendekatan kuantitatif menggunakan survey deskriptif analitik dengan pendekatan cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
4
6
0
4
Order By: Relevance
“…Moreover, the organizational members who obtain the job satisfaction will also have a high commitment. These results are in line with the studies conducted by Zeinabadi & Salehi (2011); Fraga et al (2015); Prabowo et al (2016) disclosing that the job satisfaction effects the organizational commitment.…”
Section: Organizational Commitmentsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, the organizational members who obtain the job satisfaction will also have a high commitment. These results are in line with the studies conducted by Zeinabadi & Salehi (2011); Fraga et al (2015); Prabowo et al (2016) disclosing that the job satisfaction effects the organizational commitment.…”
Section: Organizational Commitmentsupporting
confidence: 91%
“…Furthermore, the organizational members who have obtained job satisfaction will also hold a high commitment. It is in line with the results of the researches conducted by Zeinabadi & Salehi (2011), Prabowo et al (2016) who state that the job satisfaction affects the organizational commitment. In addition, studies conducted by McKinnon et al (2003) and Al-Amin and Noermijati (2010), show that the organizational culture influences the organizational commitment.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the findings are also supported by Prabowo's (2016) study which said that compensation has a positive and significant influence on organizational commitment. The study also found that compensation has an indirect effect on organizational commitment through nurse job satisfaction and contract midwives.…”
Section: The Effect Of Compensation On Job Satisfactionsupporting
confidence: 62%
“…The findings indicate that the value of the direct effect of the compensation variable on organizational commitment is greater than the indirect effect. This finding is supported by a study by Prabowo (2016) who said that compensation has a positive and significant influence on organizational commitment. The study also found that compensation has an indirect effect on organizational commitment through nurse job satisfaction and contract midwives.…”
Section: The Influence Of Compensation On Organizational Commitment Tsupporting
confidence: 56%